Gastric bypass surgery weight loss-independently induces gut Il-22 release in association with improved glycemic control in obese Zucker fatty rats - Florian Seyfried; Rebecca Springer; Annett Hoffmann; Maximilian Gruber; Christoph Otto; Nicolas Schlegel; Mohammed K. Hankir (Metabolism Open, 2023)
Background: Roux-en-Y gastric bypass surgery (RYGB) improves glycemic control in individuals with severe obesity beyond the effects of weight loss alone. To identify potential underlying mechanisms, we asked how equivalent weight loss from RYGB and from chronic caloric restriction impact gut release of the metabolically beneficial cytokine interleukin-22 (Il-22). Methods: Obese male Zucker fatty rats were randomized into sham-operated (Sham), RYGB, and sham-operated, body weight-matched to RYGB (BWM) groups. Food intake and body weight were measured regularly for 4 weeks. An oral glucose tolerance test (OGTT) was performed on postoperative day 27. Portal vein plasma, systemic plasma, and whole-wall samples from throughout the gut were collected on postoperative day 28. Gut Il-22 mRNA expression was determined by real-time quantitative PCR. Plasma Il-22 levels were determined by enzyme-linked immunosorbant assay (ELISA). Results: RYGB and BWM rats had lower food intake and body weight as well as superior blood glucose clearing capability compared with Sham rats. RYGB rats also had superior blood glucose clearing capability compared with BWM rats despite having similar body weights and higher food intake. Il-22 mRNA expression was approximately 100-fold higher specifically in the upper jejunum in RYGB rats compared with Sham rats. Il-22 protein was only detectable in portal vein (34.1 ± 9.4 pg/mL) and systemic (46.9 ± 10.5 pg/mL) plasma in RYGB rats. Area under the curve of blood glucose during the OGTT, but not food intake or body weight, negatively correlated with portal vein and systemic plasma Il-22 levels in RYGB rats. Conclusions: These results suggest that induction of gut Il-22 release might partly account for the weight loss-independent improvements in glycemic control after RYGB, and further support the use of this cytokine for the treatment of metabolic disease.